Seasonal Distribution of Escherichia coli and Relationship Among Physicochemical Parameters in Lake Water in the Gudiyattam Area, Tamil Nadu, India - Hemath Naveen Krishnam Shankar; Porchelvan Ponnusamy (Aquatic Sciences and Engineering)
The freshwater ecosystem is deteriorating and becoming more polluted due to industrialization, urbanization, and increasing industries. This study is about the bacteriological and physicochemical properties of the lake water in Gudiyattam town and its surroundings. For this research, samples of lake water from different locations were collected monthly during the period from May 2019 to April 2020 and analyzed based on standard procedures. The physicochemical parameters and bacteriological analyses were studied for all four lakes (S1, S2, S3 and S4). The bacterial analysis results showed the presence of coliform bacteria in all lakes. The most dominant value of the MPN index for total coliform number was determined as 80,000 MPN/100mL, at S4 (Valathur) location during monsoon season. It is understood from the fecal coliform count that location S4 was again found to be dominant when compared to the other lakes, with a result of 8,500MPN/100mL in the monsoon season. The possible reason for the high bacteriological values is thought to be the mixing of drainage waters into the lakes. The MPN value was higher in the monsoon season compared to the pre-monsoon season, which indicates that agricultural runoff occurs in the monsoon season. All the lakes were contaminated with bacterial populations, especially at location S4, which needs the most attention among all the lakes. The above-selected lakes are major surveilling factors for humans for various activities.